Bi-allelic AEBP1 mutations in two patients with Ehlers–Danlos syndrome. (22nd January 2019) - Syx, Delfien; De Wandele, Inge; Symoens, Sofie; De Rycke, Riet; Hougrand, Olivier; Voermans, Nicol; De Paepe, Anne; Malfait, Fransiska
Abstract: The Ehlers–Danlos syndromes (EDSs) are a clinically and molecularly diverse group of heritable connective tissue disorders caused by defects in a wide range of genes. Recently, bi-allelic loss-of-function mutations in the adipocyte enhancer-binding protein 1 ( AEBP1 ) gene were reported in three families with an autosomal recessive EDS-like condition characterized by thin and hyperextensible skin, poor wound healing with prominent atrophic scarring, joint hypermobility and osteoporosis. Using whole exome sequencing, we identified novel bi-allelic AEBP1 variants in two unrelated adult patients, previously diagnosed with an undefined EDS type, which shows important clinical resemblance to several other EDS subtypes. Our patients present with similar cutaneous and musculoskeletal features as the previously reported patients. They also show unreported clinical features, including pectus deformity, premature aged appearance, sparse and frizzled hair, fatigue and pain. AEBP1 is ubiquitously expressed and encodes the secreted aortic carboxypeptidase-like protein (ACLP) that can bind fibrillar collagens and assist in collagen polymerization. Transmission electron microscopy studies on the patients' skin biopsies show ultrastructural alterations in collagen fibril diameter and appearance, underscoring an important role for ACLP in collagen fibril organization. This report further expands the clinical, molecular and ultrastructural spectrum associated with AEBP1 defects and highlights the complex and variable phenotype associated with this new EDS variant.